Product Antimagic Labeling of Caterpillars - Shengze Wang; Yuping Gao (Journal of Mathematics)
Let G be a graph with m edges. A product antimagic labeling of G is a bijection from the edge set EG to the set 1,2,…,m such that the vertex-products are pairwise distinct, where the vertex-product of a vertex v is the product of labels on the incident edges of v. A graph is called product antimagic if it admits a product antimagic labeling. In this paper, we will show that caterpillars with at least three edges are product antimagic by an Om  log  m algorithm.